HUBUNGAN ANTARA TRAIT KEPRIBADIAN DAN IKLIM PSIKOLOGIS SEKOLAH DENGAN SELF-EFFICACY - Lufiana Harnany Utami (Psympathic : Jurnal Ilmiah Psikologi, 2010)
This research study about the correlation between personality trait and psychological climate with teacher’s self-efficacy. Instruments used are NEO-big five scale from Costa and McCrae, teacher’s self-efficacy scales and psychological climate questionnaire. Data analyzed with statistics regression. The result shows that there is a positive and significant correlation between personality trait and self-efficacy. Traits of extraversion, conscientiousness and openness significantly contribute to self-efficacy while neuroticism and agreeableness have no significant contribution. Besides, there is also positive and significant correlation between psychological climate and self-efficacy. At last, personality traits and psychological climate at school together give contribution to self-efficacy significantly.